A compact design for narrowband optical absorber based on surface plasmon polaritons. (24th December 2020) - Hu, Xinguang; Zeng, Cheng; Xia, Jinsong; Meng, Yunji
Abstract: A compact design for realizing narrowband optical absorbers at deep subwavelength is proposed, the physical regime of which is based on the excitation of quasi-surface plasmon polariton (quasi-SPP) mode at metal–substrate interface. Due to its small intrinsic loss balanced with the radiation loss, peak absorbance exceeding 99.9% with full width at half-maximum (FWHM) 2.6 nm is achieved at normal incidence. The spatially resolved feature at fixed wavelength, with narrower angular width and high peak absorbance at larger angle of incidence for TE polarization, makes the design more suitable for potential applications in optical filters, optical measurement, biosensors, and thermal emitters.